COLON ATRESIA IN COMBINATION WITH HIRSCHSPRUNG’S DISEASE: A RARE CLINICAL CASE - S. A. Karavaeva; A. V. Kagan; A. N. Kotin; T. V. Kesaeva (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
Introduction. Hirschsprung’s disease is a congenital anomaly characterized by the absence of ganglion cells in submucosal and intramuscular layers of intestinal wall that leads to the intestinal obstruction. 70–80 % of cases are isolated malformation but it can be combined with chromosomal abnormalities and other malformations. Coexistence of Hirschsprung’s disease with intestinal atresia is extremely rare. It can cause significant difficulties in diagnostics and treatment.Material and methods. Patient A, a boy, was transferred to the surgical department at the age of two days with a history of intestinal obstruction. He had abdominal X-ray studies: intestinal obstruction. The contrast enema showed microcolon that was coiled in the pelvis. Patient was prepared to the surgical treatment. Intraoperatively colonic atresia was identified at 10 sm from the ileocecal valve. A double colostomy was performed to the child and biopsy on the level of mucous fistula was taken. Histological study showed the aganglionosis of the distal colon. At the age of 4 months, the patient underwent Soave-Swenson endorectal pullthrough procedure with intraoperative extended express-biopsy that confirmed the absence of ganglion cells in whole distal bowel. The aganglionic part was resected, the ileocecal valve with the part of the colon of 10 cm long was mobilized and the endorectal bringing the colon down to the perineum was performed by Soave – Swenson. Postoperative recovery was uneventful.Results. A high index of suspicion is required to promptly diagnose Hirschsprung’s disease in a child with colonic atresia despite the rare combination of these two anomalies. In this case the histological study allowed to recognize association of colonic atresia with Hirschsprung’s disease and helped to avoid complications after further surgery.Conclusions. Early detection of coexisting of these two anomalies helps to prevent the development of serious postoperative complications.